Modelling Exchange Rate Volatility of Somali Shilling Against US Dollar by Utilizing GARCH Models - Ali, Abdullahi Osman (International Journal of Economics and Financial Issues, 2021)
The main aim of this investigation was to model the volatility of Somali shilling against US dollar by using monthly data covering from 1950 to 2010. Further to that, this finding has adopted both symmetric and asymmetric generalized autoregressive conditional heteroscedastic (GARCH) family models in order to capture volatility clustering and leverage effect as the most stylized facts of exchange rate returns. Result from ARCH indicates presence of conditional heteroscedasticity in the residual series of exchange rate. Symmetric GARCH(1,1) model shows presence of volatility clustering and persistent coefficients of greater than one indicating that volatility is an explosive process. Results from asymmetric TCHARCH(1,1) and EGARCH(1,1) indicates presence of leverage effect in the series of exchange rate where positive news have large effect on volatility than bad news of same magnitude. This study has an important implication to investors, business and risk managers. Nevertheless, this study suggests monetary authority to print new currency and de-dollarize the economy in order to be able influence exchange rate volatility. The outcome from this finding also suggests that GARCH family models sufficiently capture the volatility of Somali shilling against US dollar. Keywords: exchange rate, Somali shilling, US dollar, conditional heteroscedasticity, volatility clustering and leverage effect JEL Classifications: F31, O24 DOI: https://doi.org/10.32479/ijefi.9788